MpMRI of the prostate: is there a role for semi-quantitative analysis of DCE-MRI and late gadolinium enhancement in the characterisation of prostate cancer?. Issue 4 (April 2019) - Cristel, G.; Esposito, A.; Briganti, A.; Damascelli, A.; Brembilla, G.; Freschi, M.; Ambrosi, A.; Montorsi, F.; Del Maschio, A.; De Cobelli, F.
Abstract : Aim: To assess whether there is a significant difference in perfusion parameters between benign and malignant prostatic lesions, focusing on semi-quantitative analysis of dynamic contrast-enhanced (DCE) magnetic resonance imaging (MRI) and presence of late gadolinium enhancement (LGE). Material and methods: Three hundred and thirteen patients who underwent multiparametric MRI (mpMRI) of the prostate and with available corresponding histology (prostatectomy or biopsy) were selected retrospectively for this study. The MRI protocol consisted of multiplanar T2-and diffusion-weighted imaging, DCE and delayed axial T1 images. Images were reviewed independently by two radiologists for LGE assessment and Prostate Imaging – Reporting and Data System (PI-RADS) scoring. For each lesion, semi-quantitative analysis of DCE-MRI was performed and the following data were evaluated: time to peak, wash-in rate, wash-out rate, brevity of enhancement, and area under the curve. The presence or absence of LGE in delayed axial T1 images was assessed qualitatively. MRI results were compared to histology. The presence of significant prostate cancer was based both on Epstein criteria (SPC) and Gleason score (GS ≥7). Results: SPC and Gleason score ≥7 tumours showed significant lower time to peak and brevity of enhancement ( p <0.001) with higher wash-in rate ( p =0.001). LGE was observed in 152/313 (49%) cases; among them 103/152 (68%) did not show SPC whereas 49/152 (32%) had SPC ( p <0.001). The presence of LGE determined a risk reduction of SPC resulting as an independent predictor at multivariate analysis (logOR=-0.78, SE 0.33, p =0.02). Conclusion: Semi-quantitative perfusion analysis and LGE may help to predict the presence/absence of a significant prostate tumour and represent a promising tool to improve mpMRI diagnostic performance. Highlights: DCE-MRI Semiquantitative parameters were associated with SPC. Postinflammatory alterations such as fibrosis showed gadolinium-contrast retention. Late gadolinium enhancement was an independent predictor of the absence of SPC.